The effect of instrumental and vocal musical experience on tone categorical perception in individuals in a Chinese dialect area - Hao, Jiayi; Zhong, Yuhuan; Li, Hong; Li, Jianbo; Zheng, Maoping (Frontiers in Education, 2023)
Previous studies have shown that music training modulates adults' categorical perception of Mandarin tones. However, the effect of music training on tone categorical perception ability in individuals in Chinese dialect areas remains unclear. Methods: We recruited three groups of college students majoring in music in Chongqing, a dialect area in southwestern China. These groups included an instrumental music group (n = 31), a vocal music group (n = 32), and an instrumental-vocalist music group (n = 30). Additionally, we recruited a group of college students who did not receive any music training (n = 32). The accuracy and reaction time of the four groups were measured using the oddball task and compared to explore the differences in their tone categorical perception ability. Results:Considering both between-tone category and within-tone category, the three music groups showed both greater accuracy and shorter reaction times than the non-music group. Regarding the three music groups, no significant differences in accuracy and reaction time were detected between the instrumental and vocal groups. However, the instrumental vocalist group outperformed both the instrumental and vocal groups in terms of accuracy and reaction time. Discussion: Results showed that music training seems to have a positive effect on the categorical perception of Mandarin tone categories in Chinese dialect areas, and demonstrated that the combination of instrumental and vocal music training can further enhance tone categorical perception. To some extent, these findings provide a theoretical basis for the improvement of individual tone perception ability in dialect areas, and provided theoretical support for music and language education.